PERSPEKTIF METAKOGNITIF GURU DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Akhsanul In’am (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2012)
Abstracts: Teachers’ meta-cognitive perspective in elementary schools’ mathematic teaching. The purpose of this research was to describe teachers’ meta-cognitive perspective in elementary schools’ mathematic teaching in the Malang Region. The approach of the research was quantitative and qualitative. The subjects were 123 elementary schools’ teachers at Malang Region. Data were collected by instrument and interview. The collected data were analyzed by means and frequency. Research results showed that in general, elementary schools’ teachers’ meta-cognitive perspective in the consciousness , cognitive strategy, and planning and re-study aspects was in a good category. Specifically, elementary schools’ teachers’ meta-cognitive perspective in teaching mathematic: (1) means of the consciousness aspect was 2.91, (2) means of the a cognitive strategy aspect was 2.75, (3) means of a planning aspect was 2.83, (4) means of a re-study aspect was 2.52.Abstrak: Penelitian ini bertujuan untuk menganalisis perspektif metakognitif guru Sekolah Dasar (SD) dalam pembelajaran matematika di Kabupaten Malang. Pendekatan penelitian yang digunakan adalah kuantitatif dan kualitatif. Subyek penelitian guru SD di Kabupaten Malang sebanyak 123 orang. Data diperoleh melalui instrumen dan wawancara. Analisis dengan rata-rata dan frekuensi. Hasil penelitian menunjukkan bahwa secara umum perspektif metakognitif guru-guru SD pada aspek kesadaran, strategi kognitif, perencanaan, dan mengkaji ulang termasuk kategori baik. Secara khusus perspektif metakognitif guru dalam pembelajaran matematika adalah: (1) pada aspek kesadaran mempunyai rata-rata sebesar 2,91, (2) aspek strategi kognitif mempunyai rata-rata sebesar 2,75, (3) aspek perencanaan mempunyai rata-rata sebesar 2,83, dan (4) aspek mengkaji ulang mempunyai rata-rata sebesar 2,52.